The use of choline chloride in ataxic disorders. Issue 5 (May 1980) - Lawrence, C M; Millac, P; Stout, G S; Ward, J W
Abstract : Fourteen patients with a variety of ataxic disorders were given choline chloride, double blind for six weeks, in an attempt to improve gait and manual dexterity. One patient withdrew before receiving the active drug, twelve patients showed no functional improvement, but one achieved greater mobility; his response, which was dose dependent, ceased when choline was stopped and was reproducible.